An Analysis of Classroom Interaction in International Classes of Economy Department of Universitas Negeri Padang - Marchelda, Aldioni; Adnan, Aryuliva (Universitas Negeri Padang, 2024)
Classroom interaction involves communication between the teacher and students, as well as among the students themselves, within the classroom setting. These interactions can significantly influence students' attitudes, either positively or negatively, particularly in International Classes within the Economy Department. The objective of this research is to explore the dynamics of interaction between lecturers and students (L-S), students and lecturers (S-L), and among students (S-S), and to assess students' attitudes towards these interactions in the International Classes of the Economy Department at Universitas Negeri Padang. This descriptive qualitative study was carried out in the International Class of the Economy Department. The research tools used were observation, a questionnaire, and interviews. Data were examined by classifying specific categories within each interaction pattern using the Flanders Interaction Analysis Categories System (FIACS). The study included 28 students and 3 lecturers. Over four observed sessions, the results showed that the predominant interaction patterns were questioning in lecturer-to-student interactions, responding in student-to-lecturer interactions, and questioning among students. The group discussion technique used in the educational process significantly influenced these patterns. Furthermore, the students displayed positive attitudes towards classroom interactions, showing enthusiasm and a desire to express and sustain their independent ideas and thoughts.